2020
DOI: 10.1016/j.jenvman.2019.109894
|View full text |Cite
|
Sign up to set email alerts
|

Integrating environmental variables by multivariate ordination enables the reliable estimation of mineland rehabilitation status

Abstract: Highlights➢ A multivariate estimation of the environmental status of rehabilitating areas is presented ➢ The method integrates processes, diversity and structure in a single estimation ➢ Rehabilitation status is successfully estimated after iron ore mining in Corumbá ➢ The approach enables tests for biases regarding single variables or variable groups ➢ Defining indicators reduces the number of variables needed for further assessments AbstractDespite the wide variety of variables commonly applied to measure di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Thus, these spectral differences were sufficient to track the land use changes and accurately quantify the effectively revegetated areas. However, the assessment of revegetation quality still requires ground monitoring [13]. Specifically, the two-step segmentation of the high-resolution images enabled the identification of small revegetated structures, such as strait slopes, indicating the suitability of the proposed methodology for this study [22].…”
Section: Assessment Of the High-resolution Satellite Image Accuracy Amentioning
confidence: 91%
“…Thus, these spectral differences were sufficient to track the land use changes and accurately quantify the effectively revegetated areas. However, the assessment of revegetation quality still requires ground monitoring [13]. Specifically, the two-step segmentation of the high-resolution images enabled the identification of small revegetated structures, such as strait slopes, indicating the suitability of the proposed methodology for this study [22].…”
Section: Assessment Of the High-resolution Satellite Image Accuracy Amentioning
confidence: 91%
“…As mentioned previously, primer bias can cause DNA amplification of certain arthropod taxa that may be more or less correlated to these vegetation parameters and therefore result in differences between primers used. Apart from the presence or absence of certain taxa, for a complete assessment of environmental rehabilitation status, functional diversity should also be taken into account (Gastauer et al, 2020a). We found the compositional differences in arthropod communities in the waste piles to be driven by the presence or absence of certain groups of arthropods.…”
Section: Changes In Community Compositionmentioning
confidence: 92%
“…Vegetation structure such as basal area, tree density, tree species richness and leaf area index have previously been shown to be important when assessing environmental rehabilitation status (Ruiz-Jaen and Mitchell Aide, 2005;Gastauer et al, 2020a). As arthropod diversity and composition are known to be correlated with vegetation structure (Basset et al, 2012;Zhang et al, 2016), we fitted vegetation data with arthropod community and found that the basal area and tree species richness were correlated with the detected arthropod community.…”
Section: Changes In Community Compositionmentioning
confidence: 97%
See 2 more Smart Citations